(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to explore the challenges of administrative empowerment faced by female principals of public schools affiliated with Al-Malaz Education Office in Riyadh, and the strategies for overcoming it. It also sought to determine whether statistically significant differences exist in the challenges of administrative empowerment based on academic qualification and experience. To achieve the objectives, the descriptive method was employed, using a questionnaire as data collection tool. The sample consisted of (60) female principals from public schools within Al-Malaz Education Office. The study’s found that administrative, human, and technical challenges were prevalent to a significant degree in public schools in Al-Malaz Education Office. The most prominent challenges included: the excessive administrative workload borne by principals, low levels of managerial trust between leaders and subordinates, weak conviction among administrative staff regarding the importance of implementing administrative empowerment, a lack of awareness and culture surrounding administrative empowerment, the absence of training programs aimed at enhancing principals’ technical skills, and the lack of comprehensive administrative databases within schools. Furthermore, the study found no statistically significant differences in the challenges of administrative empowerment among school principals that could be attributed to either academic qualification or experience. Based on the perspectives of the study’s participants, several recommendations were proposed to overcome the challenges of administrative empowerment. It included promoting a culture of administrative empowerment among school principals, conducting relevant training courses on administrative empowerment, developing school technology systems in alignment with empowerment principles, and providing workshops to enhance the technical skills of school principals.